Efficacy and safety of PD-1 inhibitors in recurrent or metastatic nasopharyngeal carcinoma patients after failure of platinum-containing regimens: a systematic review and meta-analysis - Jian Luo; Wanying Xiao; Fengyang Hua; Yanqing Cao; Dongxia Wang; Xicheng Wang (BMC Cancer, 2023)
Abstract Objective There is a lack of standard salvage treatment options for recurrent or metastatic nasopharyngeal carcinoma (RM-NPC) that has failed platinum-containing regimens. Breakthroughs in immunotherapy have opened up new options for these patients. However, the efficacy and safety of immunotherapy have not been clarified. This study aimed to summarize and assess the efficacy and safety of PD-1 inhibitors in patients with RM-NPC who failed platinum-containing chemotherapy. Methods Up to August 25, 2022, clinical trials of PD-1 inhibitors in RM-NPC patients who failed platinum-containing regimens were searched in the PubMed, Embase, Cochrane, and Web of Science databases. Retrieval subject terms included “nasopharyngeal carcinoma”, “metastatic”, “recurrence”, “PD-1”, and “PD-L1”. The clinical trials eligible for inclusion were systematically reviewed and meta-analyzed. Results A total of 9 studies including 842 patients with RM-NPC were included in this meta-analysis. The results showed that PD-1 inhibitors had promising efficacy in patients with RM-NPC who failed platinum-containing regimens: objective response rate (ORR) was 24% (95% confidence interval [CI] 21–26%), disease control rate (DCR) was 52% (95% CI 45–58%), 1-year progression-free survival (PFS) rate was 25% (95% CI 18–32%), and 1-year overall survival (OS) rate was 53% (95% CI 37–68%). In terms of treatment-related adverse events (AEs), the incidence of grade ≥ 3 treatment-related AEs was 19% (95% CI 13–24%). In addition, we found that PD-1 inhibitors were more effective in patients with PD-L1 positive than in patients with PD-L1 negative nasopharyngeal carcinoma who had failed platinum-containing regimens (ORR 31% (95%CI 26–35%) vs. 21% (95% CI 17–25%)). Conclusion PD-1 inhibitors may provide a survival benefit for patients with RM-NPC who have failed platinum-containing regimens and have the advantage of a good safety profile, making them a promising treatment option.